2016
DOI: 10.1371/journal.pone.0164591
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Audiometric Test Results to Determine Hearing Impairment in Patients with Rheumatoid Arthritis: Analysis of Data from the Korean National Health and Nutrition Examination Survey

Abstract: This study aimed to evaluate the association between rheumatoid arthritis (RA) and hearing impairment in the Korean adult population. Audiometric and laboratory test data from the 2010–2012 Korean National Health and Nutrition Examination Survey (KNHANES) were used for analysis. The relationship between RA and hearing impairment was analyzed, adjusting for various known risk factors associated with hearing impairment. RA was defined in the questionnaire as “RA diagnosed by a physician (yes/no) through a standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
3
10
0
Order By: Relevance
“…The hearing impairment at high frequencies may be due to vasculitis/neuritis that affects the cochlea and cochlear nerve leading to SNHL in RA patients. On the contrary to the studies revealed a positive correlation between RA and hearing impairment ( Lasso de la Vega et al., 2016 , Yildirim et al., 2016 , Jeong et al., 2016 ), Lobo FS and Rahne T in separate case control studies did not find statistically significant increase in the incidence of hearing impairment in patients with RA compared to the control groups ( Lobo et al., 2016 , Rahne et al., 2017 ). Besides, Ahmadzadeh A in a case control study of 42 RA patients compared to the age- and sex-matched healthy individuals demonstrated a significantly higher bone conduction threshold in the patients with RA in low frequencies and in the mean of 500–2000 Hz frequencies.…”
Section: Characteristic Of Hearing Impairmentmentioning
confidence: 58%
See 3 more Smart Citations
“…The hearing impairment at high frequencies may be due to vasculitis/neuritis that affects the cochlea and cochlear nerve leading to SNHL in RA patients. On the contrary to the studies revealed a positive correlation between RA and hearing impairment ( Lasso de la Vega et al., 2016 , Yildirim et al., 2016 , Jeong et al., 2016 ), Lobo FS and Rahne T in separate case control studies did not find statistically significant increase in the incidence of hearing impairment in patients with RA compared to the control groups ( Lobo et al., 2016 , Rahne et al., 2017 ). Besides, Ahmadzadeh A in a case control study of 42 RA patients compared to the age- and sex-matched healthy individuals demonstrated a significantly higher bone conduction threshold in the patients with RA in low frequencies and in the mean of 500–2000 Hz frequencies.…”
Section: Characteristic Of Hearing Impairmentmentioning
confidence: 58%
“…SNHL was the most common hearing impairment, detected by pure tone audiometry, and affects particularly high frequency, though involvement of middle and low frequencies have also been reported ( Lasso de la Vega et al., 2016 , Yildirim et al., 2016 , Jeong et al., 2016 ). Extended high frequency audiometry, which evaluates very high frequencies (>8000 Hz), can detect hearing impairment at earlier stages.…”
Section: Characteristic Of Hearing Impairmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Rheumatoid arthritis (RA) is a chronic inflammatory disease that affects 1% of the worldwide population. 1 RA leads to the destruction of the cartilage and bone due to chronic synovitis and may consequently impair joint function.…”
Section: Introductionmentioning
confidence: 99%